Shatter cones at the Keurusselkä impact structure and their relation to local jointing. (20th July 2016) - Hasch, Maximilian; Reimold, Wolf Uwe; Raschke, Ulli; Zaag, Patrice Tristan
Abstract: Shatter cones are the only distinct meso‐ to macroscopic recognition criterion for impact structures, yet not all is known about their formation. The Keurusselkä impact structure, Finland, is interesting in that it presents a multitude of well‐exposed shatter cones in medium‐ to coarse‐grained granitoids. The allegedly 27 km wide Keurusselkä impact structure was formed about 1150 Ma ago in rocks of the Central Finland Granitoid Complex. Special attention was paid in this work to possible relationships between shatter cones and local, as well as regionally occurring, fracture or joint systems. A possible shatter cone find outside the previously suggested edge of the structure could mean that the Keurusselkä impact structure is larger than previously thought. The spacing between joints/fractures from regional joint systems was influenced by the impact, but impact‐induced fractures strongly follow the regional joint orientation trends. There is a distinct relationship between shatter cones and joints: shatter cones occur on and against joint surfaces of varied orientations and belonging to the regional orientation trends. Planar fractures (PF) and planar deformation features (PDF) were found in three shatter cone samples from the central‐most part of the impact structure, whereas other country rock samples from the same level of exposure but further from the assumed center lack shock deformation features. PDF occurrence is enhanced within 5 mm of shatter cone surfaces, which is interpreted to suggest that shock wave reverberation at preimpact joints could be responsible for this local enhancement of shock deformation. Some shatter cone surfaces are coated with a quasi‐opaque material which is also found in conspicuous veinlets that branch off from shatter cone surfaces and resemble pseudotachylitic breccia veins. The vein‐filling is composed of two mineral phases, one of which could be identified as a montmorillonitic phyllosilicate. The second phase could not be identified yet. The original composition of the fill could not be determined. Further work is required on this material. Observed joints and fractures were discussed against findings from Barringer impact crater. They show that impact‐induced joints in the basement rock do not follow impact‐specific orientations (such as radial, conical, or concentric).